(untitled) (Journal of Computational Mathematics, 2004)
A two-grid method for the steady penalized incompressible Navier-Stokes equations is presented. Convergence results are proved. If h=O(H^3-s) and ε =O(H^5-2s) (s=0 (n=2); s=12 (n=3)) are chosen, the convergence order of this two-grid method is the same as that of the usual finite element method. Numerical results show that this method is efficient and can save a lot of computation time.